An Overview on Base Real-Time Shadow Techniques in Virtual Environments - Hoshang Kolivand; Mohd Shahrizal Sunar (Universitas Ahmad Dahlan, 2012)
Shadows are elegant to create a realistic scene in virtual environments. Variety types of shadow techniques encourage us to prepare an overview on all base shadow techniques. Non real-time and real-time techniques are big subdivision of shadow generation. In non real-time techniques ray tracing, ray casting and radiosity are well known and deeply described. Radiosity implemented to create very realistic shadow on non real-time scene. Although traditional radiosity algorithm is difficult to implement, we have proposed a simple one. The proposed pseudo code is easier to understand and implement. Ray tracing used to prevent of collision of movement objects. Projection shadow, shadow volume and shadow mapping are used to create real-time shadow in virtual environments. We have used projection shadow for some objects are static and have shadow on flat surface. Shadow volume used to create accurate shadow with sharp outline. Shadow mapping that is the base of most recently techniques is reconstructed. The reconstruct algorithm gives some new idea to propose another algorithm based on shadow mapping.